Identifying Immune Cell Infiltration and Hub Genes During the Myocardial Remodeling Process After Myocardial Infarction - Tian Y; Wang Z; Liang F; Wang Y (Journal of Inflammation Research, 2023)
Yuan Tian,1,* Zilin Wang,2,* Feng Liang,3,* Yi Wang1 1Department of Cardiology, Shanghai General Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, 200080, People’s Republic of China; 2Department of Radiology, Shanghai General Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, 200080, People’s Republic of China; 3Heart Center, Shanghai Chest Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, 200080, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yi Wang, Department of Cardiology, Shanghai General Hospital, Shanghai Jiao Tong University School of Medicine, NO. 100 Haining Road, Shanghai, 200080, People’s Republic of China, Tel/Fax +86 021 63241377, Email wangyi2016@sjtu.edu.cnPurpose: Myocardial remodeling after myocardial infarction (MI) is a complex repair process following myocardial injury, characterized by the infiltration of multiple types of immune cells. However, the underlying molecular mechanism of myocardial remodeling after MI remains obscure. This study aimed to identify the hub differential expression genes (DEGs) of myocardial remodeling after MI and determine the distribution of immune cells infiltrating the pathology.Methods: We downloaded GSE132143, GSE151834, and GSE176092 data from the GEO database. The GSE132143 dataset was used to identify DEGs, perform functional annotation, and screen hub genes based on protein-protein interaction (PPI) analysis. The GSE151834 dataset was used to validate the expression of hub genes. CIBERSORTx analysis was performed to explore the immune microenvironment in myocardial remodeling after MI. After conducting a literature review, we selected P3H3 to confirm the expression by utilizing immunohistochemistry and qRT-PCR. Finally, the snRNA-seq data in dataset GSE176092 was used for clarifying the expression of these hub genes in various cell clusters.Results: We found 975 DEGs in myocardial remodeling after MI. Four hub genes (P3H3, COL15A1, COL16A1, COL27A1) were identified and were verified in the GSE151834 dataset. According to immune infiltration analysis, CD4+ naive T cells, regulatory T cells, monocytes, M2 macrophages, and neutrophils were involved in the pathological process of myocardial remodeling after MI. Additionally, in vitro experiments verified that P3h3 expression was significantly elevated in myocardial remodeling after MI. The snRNA-seq data analyzed that P3h3, Col15a1, Col16a1, and Col27a1 were highly expressed in fibroblasts of post-MI.Conclusion: This study identified four hub genes P3H3, COL15A1, COL16A1, and COL27A1, particularly P3H3, as potential targets for targeted therapy in MI patients.Keywords: myocardial infarction, myocardial remodeling, hub genes, immune infiltration, bioinformatic analysis